2015
DOI: 10.7554/elife.05506
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms underlie oral vs aboral regeneration in the cnidarian Hydractinia echinata

Abstract: Cnidarians possess remarkable powers of regeneration, but the cellular and molecular mechanisms underlying this capability are unclear. Studying the hydrozoan Hydractinia echinata we show that a burst of stem cell proliferation occurs following decapitation, forming a blastema at the oral pole within 24 hr. This process is necessary for head regeneration. Knocking down Piwi1, Vasa, Pl10 or Ncol1 expressed by blastema cells inhibited regeneration but not blastema formation. EdU pulse-chase experiments and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(153 citation statements)
references
References 55 publications
6
132
0
Order By: Relevance
“…These data are consistent with the known endodermal early neurogenesis in hydrozoans and their later migration to the epidermis. In the lower part of the adult body column, an area rich in proliferative progenitor cells (Bradshaw et al, 2015), double fluorescence ISH (dFISH) showed that only SoxB2 was expressed while, in more oral parts, most SoxB2 + cells also expressed SoxB3 (Figures 1E’–1E’’’’). Small numbers of cells, located mostly in the head area, were positive for only one gene (Figures 1E’ and S3H).…”
Section: Resultsmentioning
confidence: 99%
“…These data are consistent with the known endodermal early neurogenesis in hydrozoans and their later migration to the epidermis. In the lower part of the adult body column, an area rich in proliferative progenitor cells (Bradshaw et al, 2015), double fluorescence ISH (dFISH) showed that only SoxB2 was expressed while, in more oral parts, most SoxB2 + cells also expressed SoxB3 (Figures 1E’–1E’’’’). Small numbers of cells, located mostly in the head area, were positive for only one gene (Figures 1E’ and S3H).…”
Section: Resultsmentioning
confidence: 99%
“…Those tools, in combination with “omics” and functional genomics approaches (Momose and Houliston, 2007; Rentzsch et al, 2008; Amiel et al, 2009; Chera et al, 2009; Genikhovich and Technau, 2009; Boehm et al, 2012; Röttinger et al, 2012; Layden et al, 2013; Lapébie et al, 2014; Bradshaw et al, 2015) as well as with the recently developed techniques for genome editing (Ikmi et al, 2014) are now opening new opportunities to functionally and thoroughly address the developmental and regenerative program of cnidarian muscles systems, but also the role(s) that epitheliomuscular cells, muscle fibers and muscle contraction can play on the regeneration process.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of cnidarians has emerged in the past decades as experimental models in molecular, cell and developmental biology, providing insights into the evolution of developmental programs, including regeneration, stem cell biology and the evolution of key bilaterian traits (Kraus et al, 2007, 2016; Momose and Houliston, 2007; Amiel et al, 2009; Chera et al, 2009; Boehm et al, 2012; Layden et al, 2012; Röttinger et al, 2012; Sinigaglia et al, 2013; Leclère and Rentzsch, 2014; Abrams et al, 2015; Bradshaw et al, 2015; Helm et al, 2015; reviewed in Technau and Steele, 2011; Layden et al, 2016; Leclère et al, 2016; Rentzsch and Technau, 2016). The main, but not exclusive, cnidarian models are the medusozoan hydrozoans Hydra, Hydractinia, Podocoryna and Clytia (reviewed in Houliston et al, 2010; Galliot, 2012; Plickert et al, 2012; Gahan et al, 2016; Leclère et al, 2016) as well as the anthozoans Nematostella vectensis (reviewed in Layden et al, 2016; Rentzsch and Technau, 2016) and the coral Acropora (Shinzato et al, 2011; Hayward et al, 2015; Okubo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…42 Although further studies to support this hypothesis have to be conducted, a connection of the somatic expression of piwi and vasa genes and the regenerative capacity in Nematostella seems to be a valid possibility.…”
Section: Discussionmentioning
confidence: 99%